'Re‐placing' professional practice. (1st April 2021) - Roberts, Philip; Cosgrave, Catherine; Gillespie, Judy; Malatzky, Christina; Hyde, Sarah; Hu, Wendy CY; Bailey, Jannine; Yassine, Tagrid; Downes, Natalie
Abstract: While preparation for professional practice is conceived as placeless, it is enacted in place. Consequently, many professionals find themselves working in conditions significantly different than those they were educated in and for. This is especially relevant for new professionals arriving in rural settings after preparation in urban programs, where metrocentric models of orientation to practice are implicitly privileged. The consequent dis‐join between practice and place often results in new professionals feeling 'out of place' and questioning their professional competence. It also results in settings outside the metrocentric norm being viewed as less desirable practice contexts. Negative desirability hinders professional recruitment, while feeling out of place and incompetent hinders professional retention; both are longstanding issues in rural communities. Recent developments in professional education and practice standards emphasise adaptability to practise in specific contexts. However, 'context, ' a primary focus to date for rural preparation is presented as a largely static backdrop that needs to be accommodated to engage in the 'real practice' one was trained for. Drawing on the spatial turn in social theory, we argue that place both shapes and is shaped by professionals and their practices and as such, must be engaged with deeply and dynamically. This conceptualisation of the relationship between place and practice has critical implications for professional preparation. As interdisciplinary practitioners and researchers working in diverse contexts, we examine 'place' from a social constructivist perspective as a focal point for professional preparation.